Wynd. Book two, The secret of the wings - Tynion, James, IV; Tynion, James, IV; Dialynas, Michael (Boom! Box, 2022)
"Wynd, Oakley, Thorn, and Yorik take the next step in their dangerous quest across Esseriel, but are soon attacked by a mysterious enemy. Can Wynd rise to the moment and if so, at what cost? And when Wynd is captured and taken to the Faeries' hidden capital deep in the Weird Woods, his friends must rescue him before he's put on trial ... and Basil, Titus, and Ash unknowingly lead an even greater threat to the Faerie City--Vampyres!"--